INFORMATION TECHNOLOGIES IN LEGAL ACTIVITY - Trintina, N.; Kotelevets, S. (Physical and Mathematical Education, 2021)
Problem formulation. The article considers the current areas of use of information technology in legal activities. In today's world, one of the most important tasks of legal activity is the timely and full provision of lawyers with reliable and up-to-date legal information, as well as information that includes changes and additions to regulations, and the use of information technology in the process of examination and adoption of  important legal decisions.Materials and methods. The materials of the article are scientific works, which consider the problems of legal informatics, information relating to certain areas of use of information technology in legal activities. Method: analysis of information systems, generalization of the received facts, classification of the information technologies which are put in legal activity.Results. The directions of using information technologies in legal activity are defined and generalized: informatization of law enforcement activity, informatization of law - making, bringing legislation in line with newly adopted normative acts, improvement of legislation system for absence of contradictory normative acts, improvement of law - making process, informatization of law - making activity. All legal information resources presented on the Internet should be classified into the following: public authorities, legal media on the Internet, legal sites, virtual clubs and legal forums, human rights organizations and law firms, WWW-pages of famous lawyers, foreign legal resources ..Conclusions. Further integration of information technology in the field of legal activity will significantly reduce the time spent on decision-making within a specific legal situation, improve quality and develop the right decision.
Keywords: information technologies; legal activity; directions; search; examination; analysis; justice